Development of the online games usage purposes scale (ogups) and testing its psychometric properties - Korkın Varanok, Özgenur; Şahin, Ekrem Sedat (Journal of Dependence, 2024)
Objective: The aim of this study is develop a measurement tool to determine the usages purposes of adolescents in online games and to test their psychometric properties. Method: The study group of the research consists of 544 (272 female, 272 male) adolescent individuals reached by convenient sampling method. The development process of the Online Games Participation Purposes Scale started with a literature review. An item pool was created by supplementing the data obtained from the literature review with data obtained from two focus group interviews and six individual interviews. The construct validity of the scale was examined with Exploratory and Confirmatory Factor Analysis. The reliability of the scale was evaluated within the scope of internal consistency and stability. Results: As a result of the Exploratory Factor Analysis, it was determined that the scale had 16 items and a threedimensional structure. The fit indices obtained as a result of Confirmatory Factor Analysis were χ²/df = 2.04; GFI=.89; IFI=.96; TLI=.95, CFI=.96, and RMSEA=.07. McDonald’s Omega (ω) coefficient calculated to determine the internal consistency of the overall scale was .93; The Pearson Product Moments correlation coefficient calculated to determine its stability was found to be .80. Conclusion: The scale can be said to be a valid and reliable scale that can be used to determine the purposes of adolescents’ participation in online games.